Analysis of the Selection and Implementation of Construction Contract Types in Indonesia from the Perspective of Goods and Services Procurement Law; (Completeness of Planning Products as Procurement Documents) - Nana Arthana (Green Publisher Indonesia, 2026)
The inconsistency between the selection of construction contract types and the completeness of planning products as tender documents has become a persistent problem in Indonesian government procurement, frequently leading to variation orders, cost overruns, risk misallocation, and audit findings. This research aims to analyse the legal relationship between the completeness of planning products and the selection of construction implementation contract types, as well as to identify the legal implications of such mismatches under Indonesia's goods and services procurement law. This study employs a normative legal research method using a conceptual approach and case studies of sports stadium renovation projects. The analysis is carried out through Lawrence M. Friedman's Legal Systems Theory, which encompasses three components: the substance of the law, legal structure, and legal culture. The results of the study show that the lack of synchronisation between contract types and the readiness of tender documents constitutes a systemic failure. The substance of the law has not provided operational parameters; the institutional structure does not perform a control function from the planning stage; and the prevailing legal culture remains oriented toward the transfer of risk and the shifting of responsibility rather than sound technical planning. The study recommends establishing minimum standards of planning completeness as a prerequisite for the qualification of tender documents for lump sum contract types, strengthening the role of Construction Management (Manajemen Konstruksi) from the initial planning stage, and shifting the paradigm toward technical data-based risk management.